Informe macrofinanciero y de gestión 2012 sector departamental, municipal, salud y entidades descentralizadas vigencia 2012 (2013)
The local comptroller of Quindío Department is an entity in charge of supervising any negotiation of the public administration as well as the results generated by any other entity as it is said in its mission logo “to safeguard and to recover the public and environmental resources. The absence of a control system allows actions against the common welfare and the heritage of the nation; likewise it is necessary to ask for detailed explanation about any action taken by any control entity in a very clear, organized, easy way to understand it. Thus, it can show a real panorama ofeach public entity´s situation to take any continuous correction and improvement action.